Γ‐Glutamyltransferase and Risk of Sudden Cardiac Death in Middle‐Aged Finnish Men: A New Prospective Cohort Study. Issue 2 (8th February 2016) - Kunutsor, Setor K.; Khan, Hassan; Laukkanen, Jari A.
Abstract : Background: γ‐Glutamyltransferase (GGT) has been linked to an increased risk of several cardiovascular outcomes; however, the relationship of GGT with sudden cardiac death (SCD) has not been investigated previously. We aimed to assess the association of GGT with risk of SCD. Methods and Results: Serum GGT activity was assessed at baseline in the Kuopio Ischemic Heart Disease prospective cohort of 1780 men, and 136 SCDs were recorded during 22 years of follow‐up. Correction for within‐person variability was made using data from repeated measurements taken several years apart. The regression dilution ratio of loge GGT adjusted for age was 0.68 (95% CI 0.61–0.74). Serum GGT was log‐linearly associated with risk of SCD. The hazard ratio for SCD per 1 SD higher baseline loge GGT values (2‐fold higher) was 1.30 (95% CI 1.10–1.54; P =0.002) after adjustment for several established risk factors and remained consistent with further adjustment for alcohol consumption, resting heart rate, lipids, and C‐reactive protein (hazard ratio 1.26, 95% CI 1.05–1.50; P =0.014). The corresponding hazard ratios were 1.48 (95% CI 1.15–1.89; P =0.002) and 1.40 (95% CI 1.07–1.82; P =0.014) after correction for within‐person variability. Hazard ratios remained unchanged after accounting for incident coronary events and did not vary importantly by levels or categories of prespecified conventional risk factors. Conclusions: GGT is positively, log‐linearly, and independently associated with future risk of SCD in the general male population. Further research is needed to replicate these findings.